ANALISIS KONTRIBUSI PEMUNGUTAN PAJAK ALAT-ALAT BERAT DALAM MENINGKATKAN PENERIMAAN PAD DI PROVINSI SUMATERA UTARA - , Puja Rizqy Ramadhan (JURNAL PERPAJAKAN, 2020)
This study aims to analyze the contribution of heavy equipments tax and to find out what is the obstacles and also the effect of the heavy equipment tax revenue of the locally-generated revenue of North Sumatra Province. The analysis method which is used in this study is descriptive data which supported by qualitativeapproach, that is method which is done by using tax collection system of Office assessment system and using the principle of regulerend function. The results of this study indicate the contribution of heavy equipment tax on revenue from the original region from 2012 to 2016 is still in the category of very less and there isa decline in 2013. The impact that resulted from the heavy equipment tax revenue to the development of public facilities in the province of North Sumatra is very less to contribute due to obstacles faced by the local government in the efforts of heavy equipment tax collection and misunderstanding in communication between local government and taxpayers.